2008
DOI: 10.1101/lm.1002508
|View full text |Cite
|
Sign up to set email alerts
|

Medial auditory thalamus inactivation prevents acquisition and retention of eyeblink conditioning

Abstract: The auditory conditioned stimulus (CS) pathway that is necessary for delay eyeblink conditioning was investigated using reversible inactivation of the medial auditory thalamic nuclei (MATN) consisting of the medial division of the medial geniculate (MGm), suprageniculate (SG), and posterior intralaminar nucleus (PIN). Rats were given saline or muscimol infusions into the MATN contralateral to the trained eye before each of four conditioning sessions with an auditory CS. Rats were then given four additional ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 53 publications
9
52
0
Order By: Relevance
“…However, unilateral stimulation of the LGN, SC, or VCTX in the hemisphere contralateral to the conditioned eye was sufficient for eyeblink conditioning in rats in the present study, suggesting that the necessary visual CS pathway for cerebellar learning may be primarily unilateral. Unilateral CS input has been demonstrated for the auditory CS pathway in rats, where the inputs to the PN that are necessary for eyeblink conditioning arise from the inferior colliculus and medial auditory thalamus in the hemisphere contralateral to the conditioned eye (Halverson and Freeman 2006;Campolattaro et al 2007;Halverson et al 2008). Inactivation or lesion studies are needed to determine whether the visual CS pathway for eyeblink conditioning is unilateral.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, unilateral stimulation of the LGN, SC, or VCTX in the hemisphere contralateral to the conditioned eye was sufficient for eyeblink conditioning in rats in the present study, suggesting that the necessary visual CS pathway for cerebellar learning may be primarily unilateral. Unilateral CS input has been demonstrated for the auditory CS pathway in rats, where the inputs to the PN that are necessary for eyeblink conditioning arise from the inferior colliculus and medial auditory thalamus in the hemisphere contralateral to the conditioned eye (Halverson and Freeman 2006;Campolattaro et al 2007;Halverson et al 2008). Inactivation or lesion studies are needed to determine whether the visual CS pathway for eyeblink conditioning is unilateral.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using lesions, inactivation, stimulation, and neural tract tracing have provided evidence that the auditory CS pathway that is necessary for acquisition and retention of eyeblink conditioning is comprised of converging inputs to the medial auditory thalamic nuclei (MATN), and a direct ipsilateral projection from the MATN to the PN (Halverson and Freeman 2006;Campolattaro et al 2007;Freeman et al 2007;Halverson et al 2008). Unilateral lesions of the MATN, contralateral to the conditioned eye, block acquisition of eyeblink CRs to a tone CS but have no effect on conditioning with a light CS (Halverson and Freeman 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter two groups did not differ significantly from each other (P=0.356; Figure 3B). In addition, a separate oneway repeated measures ANOVA revealed that the simple main effects of session on the CR peak amplitude were significant for both the delay [F (9,63) =5.143, P<0.001] and shorttrace [F (9,72) =4.529, P<0.001] conditioned groups, but not for the long-trace conditioned group [F (9,81) =0.873, P=0.554; Figure 3B]. …”
Section: Acquisition Of Eyeblink Conditioning By the Guinea Pigsmentioning
confidence: 99%